2003
DOI: 10.1128/aem.69.10.6000-6006.2003
|View full text |Cite
|
Sign up to set email alerts
|

Compound-Specific Isotopic Fractionation Patterns Suggest Different Carbon Metabolisms among Chloroflexus -Like Bacteria in Hot-Spring Microbial Mats

Abstract: Stable carbon isotope fractionations between dissolved inorganic carbon and lipid biomarkers suggest photoautotrophy by Chloroflexus-like organisms in sulfidic and nonsulfidic Yellowstone hot springs. Where co-occurring, cyanobacteria appear to cross-feed Chloroflexus-like organisms supporting photoheterotrophy as well, although the relatively small 13 C fractionation associated with cyanobacterial sugar biosynthesis may sometimes obscure this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
63
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 46 publications
2
63
0
Order By: Relevance
“…or the diol glycosides that are abundant in R. castenholzii. In agreement, both alkenes and diol glycosides are also only minor compounds in these mats (44,45).…”
supporting
confidence: 69%
See 1 more Smart Citation
“…or the diol glycosides that are abundant in R. castenholzii. In agreement, both alkenes and diol glycosides are also only minor compounds in these mats (44,45).…”
supporting
confidence: 69%
“…into polyglucose is transferred to FAPs via assimilation of [ 13 C]acetate derived from cyanobacterial fermentation (46). Compound-specific stable carbon isotope studies of FAP biomarkers also suggested that FAPs may be photoautotrophic (42,45). FAPs that assimilate carbon which has been fixed and then excreted by cyanobacteria should have stable carbon isotope signatures typical of those resulting from the Calvin cycle.…”
mentioning
confidence: 99%
“…Photoautotrophy by obligately phototrophic GNSLB in sulfidic hot springs has been described previously (13), and the potential for autotrophy in nonsulfidic mats has been suggested by 3-(3,4-dichlorophenyl)-1,1-dimethylurea inhibition of oxygenic photosynthesis and sulfide stimulation experiments (4). The natural abundance of stable carbon isotopic compositions of typical Chloroflexus lipids, such as wax esters and long-chain alkenes (45,49), suggests that GNSLB are autotrophic in sulfidic mats (46,48), as typical Chloroflexus lipids had stable carbon isotope values that were in agreement with inorganic carbon fixation via the 3-hydroxypropionate carbon fixation pathway (19,49). In sulfidic mats, where the sulfide concentration is low enough for cyanobacteria to be present, the stable carbon isotopic composition of Chloroflexus-specific lipids suggests mixotrophic metabolism of the GNSLB population (48).…”
mentioning
confidence: 87%
“…The predominant GNSLB in nonsulfidic, alkaline, siliceous hot spring microbial mats are closely related to Roseiflexus castenholzii (30) and might therefore have the potential for heterotrophic metabolism (17). The stable carbon isotopic composition of wax esters typical for Roseiflexus (M. T. J. van der Meer, S. Schouten, J. S. Sinninghe Damsté, M. T. Madigan, and D. M. Ward, unpublished data) and Chloroflexus (48) found in such mats seems to suggest autotrophy as the dominant carbon acquisition mechanism.…”
mentioning
confidence: 98%
See 1 more Smart Citation